What Ever Happened to Modernism? de Gabriel Josipovici - Stephen Mitchelmore (Revue LISA, 2014)
Gabriel Josipovici’s What Ever Happened to Modernism? (2010) drew great attention to a critic and novelist otherwise rarely mentioned in the literary pages of the mainstream press. Its framing and misrepresentation of the content of the book, however, merely confirmed the necessity of Josipovici’s project to reinvigorate critical discourse in the arts – specifically literature in the United Kingdom. In addition to tracing the book’s themes through Josipovici’s earlier critical works, this essay contrasts its reception with a précis and critical commentary of the book’s argument with emphasis on summarising its key themes: the disenchantment of the world, the inward debate of authority, the elimination of choice, and the imitation of an action.